Rho‐kinase pathway activation and apoptosis in circulating leucocytes in patients with heart failure with reduced ejection fraction. Issue 2 (28th November 2019) - Ocaranza, Maria Paz; Moya, Jackeline; Jalil, Jorge E.; Lavandero, Sergio; Kalergis, Alexis M.; Molina, Cristián; Gabrielli, Luigi; Godoy, Iván; Córdova, Samuel; Castro, Pablo; Mac Nab, Paul; Rossel, Victor; et al.
Abstract: Background: Increased Rho‐kinase activity in circulating leucocytes is observed in heart failure with reduced ejection fraction (HFrEF). However, there is little information in HFrEF regarding other Rho‐kinase pathway components an on the relationship between Rho‐kinase and apoptosis. Here, Rho‐kinase activation levels and phosphorylation of major downstream molecules and apoptosis levels were measured for the first time both in HFrEF patients and healthy individuals. Methods: Cross‐sectional study comparing HFrEF patients (n = 20) and healthy controls (n = 19). Rho‐kinase activity in circulating leucocytes (peripheral blood mononuclear cells, PBMCs) was determined by myosin light chain phosphatase 1 (MYPT1) and ezrin‐radixin‐moesin (ERM) phosphorylation. Rho‐kinase cascade proteins phosphorylation p38‐MAPK, myosin light chain‐2, JAK and JNK were also analysed along with apoptosis. Results: MYPT1 and ERM phosphorylation were significantly elevated in HFrEF patients, (3.9‐ and 4.8‐fold higher than in controls, respectively). JAK phosphorylation was significantly increased by 300% over controls. Phosphorylation of downstream molecules p38‐MAPK and myosin light chain‐2 was significantly higher by 360% and 490%, respectively, while JNK phosphorylation was reduced by 60%. Catecholamine and angiotensin II levels were significantly higher in HFrEF patients, while angiotensin‐(1‐9) levels were lower. Apoptosis in circulating leucocytes was significantly increased in HFrEF patients by 2.8‐fold compared with controls and significantly correlated with Rho‐kinase activation. Conclusion: Rho‐kinase pathway is activated in PMBCs from HFrEF patients despite optimal treatment, and it is closely associated with neurohormonal activation and with apoptosis. ROCK cascade inhibition might induce clinical benefits in HFrEF patients, and its assessment in PMBCs could be useful to evaluate reverse remodelling and disease regression.